2008
DOI: 10.1111/j.1537-2995.2008.01910.x
|View full text |Cite
|
Sign up to set email alerts
|

A nationwide survey for hepatitis E virus prevalence in Japanese blood donors with elevated alanine aminotransferase

Abstract: HEV markers (HEV RNA and anti-HEV) were detected in donors with elevated ALT levels who were widely distributed over Japan. The prevalence and incidence were higher in eastern Japan than in western Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
65
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(77 citation statements)
references
References 26 publications
12
65
0
Order By: Relevance
“…The seroprevalence rates observed in this study (donors with nonelevated ALT, 6%; donors with elevated ALT, 5.88%) are more comparable to rates which have been observed for Switzerland and Japan than to those observed for Germany so far. The seroprevalence rates of anti-HEV IgM have been measured less frequently, but studies in Chinese blood donors revealed a seroprevalence rate of 0.94 to 1.8% (11,21), comparable to 0.5 to 1.6% in Japan (18,20,42) and the 0.5% observed in this study. We also observed a considerably higher seroprevalence rate of 8.08% in donors with elevated ALT levels, according to data obtained by Fukuda et al (3.3%) (18).…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The seroprevalence rates observed in this study (donors with nonelevated ALT, 6%; donors with elevated ALT, 5.88%) are more comparable to rates which have been observed for Switzerland and Japan than to those observed for Germany so far. The seroprevalence rates of anti-HEV IgM have been measured less frequently, but studies in Chinese blood donors revealed a seroprevalence rate of 0.94 to 1.8% (11,21), comparable to 0.5 to 1.6% in Japan (18,20,42) and the 0.5% observed in this study. We also observed a considerably higher seroprevalence rate of 8.08% in donors with elevated ALT levels, according to data obtained by Fukuda et al (3.3%) (18).…”
Section: Discussionmentioning
confidence: 53%
“…Approximately 10% of plasma pools were positive for HEV RNA (sources, North America, Europe, and Southeast Asia) (4), and the rate of individual HEV RNA-positive donors varies from 1:7,986 (Sweden, 0.012%) to 1:4,525 (Germany, 0.022%) (2) to 1:7,040 (United Kingdom, 0.014%) (24). Other studies from Asia revealed hepatitis viremia of 0.07% (China) (21) and 0.3% (Japan) (18) among blood donors and donors with an elevated ALT level of 1.1% (42). In the present study, we even observed a considerably higher rate of 1:1,240 HEV RNA-positive donors (0.08%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the globally ubiquitous zoonotic HEV strains (genotypes 3 and 4) have more recently been identified as a cause of sporadic hepatitis in medically vulnerable patients and the general population in high-income countries. [4][5][6][7][8][9][10][11][12][13][14] High case-fatality ratios among pregnant women, particularly during the third trimester of pregnancy, remain an almost pathognomonic feature of hepatitis E epidemics caused by HEV genotype 1. [15][16][17][18][19][20][21] There is mounting evidence that hepatitis E is an important contributor to maternal morbidity and mortality in south Asia, even outside of periodic large outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…For the surveys of HEV prevalence in blood donors, we tested samples of the donors who were disqualified due to high ALT level over 200 IU ⁄ l [4]. Samples of donors with ALT elevation during the 1-year period from April 2003 were collected from all-over Japan and tested for HEV markers: IgM anti-HEV, IgG anti-HEV and HEV RNA.…”
mentioning
confidence: 99%